2021
DOI: 10.4103/jehp.jehp_35_21
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of students' academic resilience in the relationship between self-efficacy and test anxiety

Abstract: BACKGROUND: There is growing acknowledgment that medical education can be a stressful experience for students and may have a devastating effect on their psychological well-being. The present article, therefore, aimed at investigating students' academic resilience as a mediating variable in self-efficacy-test anxiety relation. MATERIALS AND METHODS: In this cross-sectional correlational study, a convenience sample of 243 medical students was selected and participated, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
(82 reference statements)
2
8
0
Order By: Relevance
“…In addition, the criterion validity results of the academic resilience scale showed that there was a moderately positive and significant relationship between the academic resilience scale and its subscales and the general self-efficacy scale, and this result confirmed the criterion validity of the scale (r= .55; p <0.01). This result is consistent with previous research findings that there is a positive relationship between academic resilience and self-efficacy (Hayat et al, 2021;Rajan et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the criterion validity results of the academic resilience scale showed that there was a moderately positive and significant relationship between the academic resilience scale and its subscales and the general self-efficacy scale, and this result confirmed the criterion validity of the scale (r= .55; p <0.01). This result is consistent with previous research findings that there is a positive relationship between academic resilience and self-efficacy (Hayat et al, 2021;Rajan et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, self-efficacy plays a significant role in fostering resilience ( Kumfer, 1999 ; Cody, 2013 ; Rees et al, 2015 ), which has been confirmed as the strongest predictor of professional identity ( Bhattarai et al, 2020 ; Zhang et al, 2021 ). However, no empirical study has examined the mediating role of resilience in the relationship between self-efficacy and professional identity ( Hayat et al, 2021 ; Ma et al, 2021 ). Lastly, role models play an important role in the development of professional identity in FNS ( Paice, 2002 ; Sternszus et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to test this effect. This refers to the results of Hayat's (2021) study, which found that academic resilience significantly mediated the relationship between self-efficacy and student exam anxiety with a score (β = −0.108, P < 0.0001). Meanwhile, Najla (2020), in her study, explained that resilience has a significant effect of 20.5% on student academic procrastination.…”
Section: Introductionmentioning
confidence: 56%